A COMPARISON OF A DIVIDED AND A SINGLE DOSE REGIME OF DOTHIEPIN AND ITS THERAPEUTIC EFFICACY - Sharma, S. D. (Medknow Publications, 1981)
In a double-blind study the advantages of a once-a-day dosage of a tricyclic antidepressant as against a thrice daily dosage regimen was evaluated using dothiepin (Prothiaden) and matching placebo tablets. Twenty eight adult patients of both sexes participated in the study and were randomly allocated to drug treatment. Out of 28 patients who received dothiepin, 17 showed good improvement, in 6 improvement was fair and in 5 there was no improvement. These findings show that the response to dotheipin was satisfactory. Further, both treatments were equally effective in relieving symptoms of depression.